Synthesis of Na-Pumice catalyst for heterogeneous transesterification of soybean oil optimization, kinetics, and reusability studies - Cuasay, Jodel L.
Sodium-loaded pumice (Na-Pumice) catalyst was synthesized for the heterogeneous base transesterication of soybean oil into biodiesel. Na-Pumice catalyst was prepared through wet impregnation of the pumice support material with NaOH solutions followed by calcination at an elevated temperature of 120oC. Analytical techniques such as X-ray diffraction (XRD), scanning electron microscopy with energy dispersive X-ray (SEM-EDX) spectroscopy, and Brunauer-Emmett-Teller (BET) surface analysis were then used to characterize the prepared catalyst. Response surface methodology (RSM) based on three-level, three-factor Box-Behnken design was employed to design a series of experiments to optimize the transesterification reaction. Reaction time, methanol to oil molar ratio, and amount of catalyst were the optimized process variables with the fatty acid methyl ester (FAME) yield as the response variable. The optimum reaction conditions were X1 (reaction time, h) = 2.75, X2 (amount of catalyst, %wt) = 12.86, and X3 (methanol/oil molar ratio) = 24:1, with a predicted conversion of 100%. The kinetics of the process and the reusability of the catalyst were also studied. Reaction kinetics at optimum conditions were found to agree with a pseudo-first order model. The catalyst was tested for three successive cycles and maintained 99% methyl ester conversion.